2018
DOI: 10.4236/psych.2018.96084
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being and Self-Efficacy in Life Skills among Italian Preadolescents with Positive Body Esteem: Preliminary Results of an Intervention Project

Abstract: The main purpose of this project will be to increase the psychological well-being, self-efficacy in life skills, and body esteem in a group of Italian preadolescents who will participate in the life skills training. This project will be divided into three phases consisting of a verification of the changes that will take place following the realization of laboratory activities useful to enhance the psychological well-being of students in the scholastic context. For the first phase, an exploratory analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Babakhani, 2011;Rezayat & Nayeri, 2013). Likewise, Sagone, De Caroli, Indiana, & Fichera (2018) found that, after the life skills training about self-image and sociorelational competences, preadolescents enhanced their self-efficacy only in the managing of negative emotions and some factors of psychological well-being. We will address future investigations towards the improvement of psychological well-being, resilient resources, optimism, coping strategies, and assertiveness in children and adolescents with disability (sensorial, intellectual, or behavioural disability) or social disadvantages through the life skills training performed in school context, defining the array of activities useful to refine on the quality of life of each student.…”
Section: Conclusion and Future Directionmentioning
confidence: 90%
“…Babakhani, 2011;Rezayat & Nayeri, 2013). Likewise, Sagone, De Caroli, Indiana, & Fichera (2018) found that, after the life skills training about self-image and sociorelational competences, preadolescents enhanced their self-efficacy only in the managing of negative emotions and some factors of psychological well-being. We will address future investigations towards the improvement of psychological well-being, resilient resources, optimism, coping strategies, and assertiveness in children and adolescents with disability (sensorial, intellectual, or behavioural disability) or social disadvantages through the life skills training performed in school context, defining the array of activities useful to refine on the quality of life of each student.…”
Section: Conclusion and Future Directionmentioning
confidence: 90%
“…The component of body experience and selfassessment with respect to one's own body has its own relevance on the aspects of psychological wellbeing linked to self-efficacy. In fact, it has been demonstrated that self-efficacy, both general and specific, in daily life is linked to the psychological well-being of individuals (Sagone et al, 2018). In this particular age group, high self-efficacy is also associated with better school performance (Fortman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of what has emerged, it is desirable that in this phase of post-pandemic recovery, good practices, also promoted by school systems, are taken into consideration to activate students' resources. To this end, it may be useful to activate programs aimed at enhancing physical activity to promote healthy lifestyles and encourage body knowledge/awareness and satisfaction (Sagone et al, 2018). Training aimed at working on self-esteem at the physical/body level and on self-efficacy to promote positive development and a state of psycho-physical well-being, rebalancing the stressful situations experienced during the pandemic period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations